Presbyopia-correcting performance and subjective outcomes of a trifocal intraocular lens in eyes with different axial lengths: A prospective cohort study - Sun, Tong; Liu, Yiyun; Zhao, Xiaorui; Gao, Yufei; Yang, Tingting; Lan, Qianqian; Tang, Chuhao; Qi, Hong (Frontiers in Medicine, 2022)
Purpose: To compare the presbyopia-correcting performance, visual quality, satisfaction and life quality after implantation of a diffractive trifocal intraocular lens (IOL) in eyes with different axial lengths (AL). Methods: This prospective cohort study enrolled patients with implantation of a trifocal IOL. Manifest refraction, uncorrected and distance-corrected visual acuity at different distances, contrast sensitivity, aberrations and IOL decentration were measured three months after surgery. Spectacle independence, adverse photic phenomena, overall satisfaction and life quality were assessed with a questionnaire. Results: This study included 61 eyes of 61 patients: 16 eyes in the short AL group, 28 eyes in the control group and 17 eyes in the long AL group. Postoperatively, the prediction error of spherical equivalent showed a difference (P=0.002). The uncorrected near visual acuity in the long AL group was higher (P=0.047). Although a higher IOL decentration was obtained in the long AL group (P=0.034), no significant difference was found in contrast sensitivity and aberrations (all P>0.05). In the questionnaire, patients in the long AL group showed a relatively lower spectacle independence at near distance (P=0.060) and had difficulties in near activities, mental health and role in daily life (P=0.003, 0.021 and 0.033). However, no significant difference was observed in overall satisfaction (P=0.124). Conclusion: With detailed preoperative evaluation, the trifocal IOL provided satisfactory visual outcomes for patients with different AL. AL had a certain influence on predictability and IOL decentration. And for patients with long AL, the inadaptability to the near focal point might become an important problem.